Strategi Pembangunan Pariwisata Berbasis Masyarakat di Desa Oetalus Dengan Filosofi Ama’ Sa’u Nome: Community-Based Tourism Development Strategy in Oetalus Village with the Ama’ Sa’u Nome Philosophy - Anin, Helidorus F.; Sengkoen, Mariano (Undiksha, 2025)
Oetalus Village has tourism potential that can be developed, based on the characteristics of the community. The Oetalus Village Government needs a strategy that can be used as a means and direction of development, especially in accommodate and transform local wisdom in a Community-Based Tourism. This research aims to identify the determinant of internal and external environmental factors, and analyze the development strategies of Community-Based Tourism in Oetalus Village with the Ama’ Sa’u Nome way of life. This research used a descriptive qualitative approach. Data collection used questionnaires, interviews, and FGDs, and were conducted in May-August 2024. Data analysis used SWOT Matrix, using the paradigm of Community-Based Tourism. This research found that Community-Based Tourism development in Oetalus Village with the Ama’ Sa’u Nome way of life is influenced by 8 Strength conditions, 6 Weakness conditions, 8 Opportunity conditions, and 5 Threat conditions. Analysis of the SWOT Matrix shows that the development strategy of Community-Based Tourism in Oetalus Village with the Ama’ Sa’u Nome way of life lies in Quadrant I, means that Oetalus Village has strengths that can take advantage of existing opportunities. The strategy that can be applied is to support aggressive growth policies (Growth Oriented Strategy). The village government needs to institutionalize the customary forum, documenting the customary values of the village, designing a local wisdom-based tourism packaging model, and building cooperation with government agencies, non-government agencies, as well as academics and professional groups working in the tourism sector to realize the strategy.